Tribes and caste of the central provinces of India - Russell, R.V.; Lal, Rai Bahadur Hira (Delhi, 1975)
THIS book is the result of the arrangement made by the Government of India, on the suggestion of the late Sir Herbert Risley, for the preparation of an ethnological account dealing with the inhabitants of each of the principal Provinces of India. The work for the Central Provinces was entrusted to the author, and its preparation, undertaken in addition to ordinary official duties, has been spread over a number of years. The prescribed plan was that a separate account should be written of each of the principal tribes and castes, according to the method adopted in Sir Herbert Risley's Tribes and Castes of Bengal. This was considered to be desirable as the book is intended primarily as a work of reference for the officers of Government, who may desire to know something of the customs of the people among whom their work lies. It has the disadvantage of involving a large amount of repetition of the same or very similar statements about different castes, and the result is likely therefore to be somewhat distasteful to the ordinary reader. On the other hand, there is no doubt that this method of treatment, if conscientiously followed out, will produce more exhaustive results than a general account. Similar works for some other Provinces have already appeared, as Mr. W. Crooke's Castes and Tribes of the North-Western Provinces and Oudh, Mr. Edgar Thurston's Castes and Tribes of Southern India, and Mr. Ananta Krishna Iyer's volumes on Cochin, while a Glossary for the Punjab by Mr. H. A. Rose has been partly published. The articles on Religions and Sects were not in the original scheme of the work, but have In several been subsequently added as being necessary to render it a complete ethnological account of the population. instances the adherents of the religion or sect are found only in very small numbers in the Province, and the articles have been compiled from standard works.
Publish under the orders of the central provinces administration in four volumes vol. 1.
Keywords: Castes India Madhya Pradesh